Pengaruh Manajemen Bakat dan Budaya Organisasi Terhadap Kinerja Pegawai Pada BPKAD Kota Padang - Aminar Sutra Dewi; Puteri Ekacuazti Yandri (Fakultas Sastra Universitas Ekasakti, 2021)
Employee performance in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities assigned to him. This study aims to examine the effect of talent management on employee performance, to examine the influence of organizational culture on employee performance, the sampling method uses total sampling, where all members of the population are sampled as many as 63 employees at the Regional Financial and Asset Management Agency of Padang City. The data analysis technique used to test the hypothesis is multiple linear regression. The results show that talent management has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance.